Kawaii in the semiotic landscape. (13th April 2019) - Hiramoto, Mie; Wee, Lionel
Abstract : The Japanese word kawaii means 'cute', 'lovable' or 'adorable' and is used to express the quality of cuteness or kawaii aesthetics in the general context of Japanese culture. This concept has become prominent in many aspects of Japanese modern culture, including clothing, personal appearance, food, toys, behaviour and mannerisms. While entities culturally characterized as kawaii are considered adorable and delicate, they also tend to appeal to people's deep inward affections in a visceral manner. Scholarly discussions of kawaii have tended to focus on speciﬁc entities like commodiﬁed objects or school children, and these target entities are treated as relatively isolable units that happen to be imbued with kawaii attributes. Concomitantly, this also means that the question of how kawaii entities or other features associated with kawaii aesthetics might be integrated into the broader sociocultural environment has tended to remain relatively underexplored. Drawing attention to kawaii as a key component of Japanese material culture, this paper investigates selected kawaii data taken from banal civic signs in Tokyo's semiotic landscapes. We then analyse the role of kawaii in matters traditionally not associated with kawaii through the lens of affection and viscerality.